(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
In 2021 the legislator has passed a law that regulates euthanasia in very broad terms while decriminalising its practice when the legal requirements for euthanasia have been fulfilled. Its practice is entrusted exclusively to doctors, and the procedure is surrounded by numerous guarantees, prerequisites, requirements and deadlines, which could be considered as excessive bureaucratisation. This continues to be a matter for social debate.